Importance of Work-Related Psychosocial Factors in Exertion Perception Using the Borg Scale Among Workers Subjected to Heavy Physical Work - Emma Sala; Nicola Francesco Lopomo; Cesare Tomasi; Francesco Romagnoli; Alberto Morotti; Pietro Apostoli; Giuseppe De Palma; Giuseppe De Palma (Frontiers Media S.A., 2021)
Objective: This study aimed to analyse the role of several environmental and time variables, as well as individual and psychosocial factors, on the perception of exertion, expressed by using the Borg scale, on logistics workers performing heavy manual tasks.Materials and Methods: We enrolled 56 subjects working in logistics sector that were interviewed on the perceived exertion required to execute a task of manual lifting of heavy loads, by using the Borg scale. The interviews were carried out during different shifts, at different times during the shifts and during several different months of the year. We also assessed the workers' anthropometric characteristics, length of service, any musculoskeletal diseases, and physical activity outside work. Workers were also interviewed using the structured OREGE questionnaire, in order to evaluate the main symptoms of stress and work-related psychosocial risk factors.Results: Overall, the subjective perception of the strength exerted by the workers exposed to a high risk of manual handling of loads was moderate. The rating attributed using the Borg scale showed no correlation with any of the investigated variables. 100% of the workers denied to suffer from symptoms of stress, whereas in terms of psychosocial factors, the workload was globally perceived as positive.Conclusion: The study results support the hypothesis that optimal work conditions-from a psychosocial point of view-reduce the subjective perception of exertion by workers even if exposed to a high risk of biomechanical overload.